Large Eddy Simulation (LES) of flow in meandering vegetated river reach of Perak river - Goh, Huan Tao (2022)

(untitled)
Low lying ground near lower reaches of Perak River in Malaysia has been facing several problems including constant floods, erosion and sediment deposition. Due to these issues, efforts are being made by the Perak state government to reinforce the banks of Perak River in Teluk Intan, to manage the water passage and to keep the depth for navigation purposes. The erosion of the river bank and the changes of the bed bathymetry in this area are mainly caused by the effects of the meandering river flow which tend to move the surface flow toward outer bank, but are a result of complex interaction of the river flow with the movement of the bed sediment and the vegetation in the flow passage and on the banks. The aim of this study is to develop a numerical method based on an advanced Large Eddy Simulation (LES) technique to simulate the river flow characteristic in the meandering river with vegetation. The LES method solves for the large scale turbulent fluctuation including the free surface motion on fixed grid by modelling the effects of unresolved turbulent motion and the details of flow through vegetation. Several simulation calculations of the flow in meandering reach of Perak River in Teluk Intan, Perak with different conditions of vegetation and discharge rates have been conducted. Furthermore, in order to compare the simulation result with real situation, site survey has been conducted in the simulated river reach. The flow velocity distribution was measured by an ii Acoustic Doppler Current Profiler (ADCP) and the changes of the surface elevation were monitored by water level gauges, sample collection of suspended solid and sedimentation have been conducted. Results from LES simulation and site survey have been compared. In conclusion, general flow characteristics with complex bathymetry and vegetation effects can be reproduced by this LES method which can further be used to examine the effects of any changes in river bed and bank conditions.